2022
DOI: 10.1186/s42483-022-00147-9
|View full text |Cite
|
Sign up to set email alerts
|

Colletotrichum species pathogenic to strawberry: discovery history, global diversity, prevalence in China, and the host range of top two species

Abstract: Anthracnose caused by Colletotrichum species, is one of the most destructive diseases affecting strawberry production worldwide. Fungi of the genus Colletotrichum, being ancient and co-evolved with flowering plants, rank eighth among the top ten economically important fungal pathogens and have diversified to adapt to various hosts. Since it was first reported in United States in 1931, strawberry anthracnose has spread globally, resulting in devastating economic, social, and ecological consequences. In a sense,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 103 publications
0
7
1
Order By: Relevance
“…Furthermore, although in lower abundance (0.9%) species of Colletotrichum were predicted in market-derived samples. Among them, C. acutatum, known as the leading cause of anthracnosis [49,50] in strawberries, was not detected in this study. Finally, a phylogenetic tree was built to reveal evolutionary relationships and biological diversity in a sequence data set (Figure S4).…”
Section: Taxonomic Assignment Suggests Both Beneficial and Harmful Ye...contrasting
confidence: 61%
“…Furthermore, although in lower abundance (0.9%) species of Colletotrichum were predicted in market-derived samples. Among them, C. acutatum, known as the leading cause of anthracnosis [49,50] in strawberries, was not detected in this study. Finally, a phylogenetic tree was built to reveal evolutionary relationships and biological diversity in a sequence data set (Figure S4).…”
Section: Taxonomic Assignment Suggests Both Beneficial and Harmful Ye...contrasting
confidence: 61%
“…Compared to primary inoculum, secondary inoculum are more closely correlated with disease severity for polycyclic pathogens such as Colletotrichum spp. [72,73]. As different species can cause varying levels of signs on the plant parts, the location and quantity of secondary inoculum may also vary.…”
Section: Secondary Inoculum Sources and Infection Dynamicsmentioning
confidence: 99%
“…, 2015) and China (Ji et al. , 2022), and was reported to be more aggressive than C. fioriniae in the USA (Wang et al. , 2019).…”
Section: Figurementioning
confidence: 99%
“…To the best of our knowledge, this is the first report of C. nymphaeae in Egypt. Colletotrichum nymphaeae was described recently in the UK (Baroncelli et al, 2015) and China (Ji et al, 2022), and was reported to be more aggressive than C. fioriniae in the USA (Wang et al, 2019). Given the occurrence and pathogenicity of C. nymphaeae, this species is likely to be a key cause of strawberry anthracnose in Egypt and management strategies are required to prevent its further spread.…”
mentioning
confidence: 99%